Tick remains from Areni-1 (Birds’ Cave, Armenia) - Zarikian, Noushig; Dilbaryan, Kim; Gasparyan, Boris (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
Ticks have never been included in archaeological analytic studies. Here, we present the discovery of a tick from the archaeological excavations at Areni-1 Cave in the Republic of Armenia. The well preserved tick Rhipicephalus bursa provides important information about the prevailing ecology during the periods of habitation and usage of the cave by Medieval inhabitants and supports previous hypotheses, that ticks were a potential source of disease for human and other mammals especially cattle, sheep, horse and dog. This discovery has health, behavioral and ecological implications for the people that occupied the cave.